Optimization and Numerical Approximation for Micropolar Fluids - Stavre, Ruxandra (Numerical functional analysis and optimization, 2003)
In the theory of micropolar fluids, a special case appears when the microrotation is equal to the vorticity of the fluid. The aim of this article is to determine an external field which realises this case. An existence result for the proposed control problem is obtained and the necessary conditions of optimality are derived. For solving the optimality system, an iterative algorithm is proposed and its convergence is obtained. The discretization of the approximation is studied; stability and convergence theorems are proved.